Customer Satisfaction Analysis Through Service Quality for Service Strategy Improvement Mutiareads - Hana, Halimah Mardiah; Chan, Arianis; Barkah, Cecep Syafaatul; Tresna, Pratimi Wulan (Universitas Negeri Semarang, 2022)
The impact of the Covid-19 pandemic has forced MSMEs activists to survive and continue to thrive. ne of the efforts made is to use the internet in its business activities. In this day of globalization, the rapid growth of internet technology brings numerous benefits to its users, one of which is the ability to conduct sales and purchases online. As a result, there is fierce competition among MSMEs, and business actors must devise strategies that satisfy customers. One way to gratify customers is to improve service quality. Mutiareads is an example of an MSMEs that uses the internet to market its products, including new and secondhand books worth reading. Customer satisfaction is measured in this study using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (CSI) techniques based on the dimensions of reliability, empathy, tangibles, responsiveness, and assurance. The results that will be obtained from the CSI method are the overall satisfaction level of Mutiareads consumers by 86%. The results of the IPA calculation are that there are 2 attributes that need to be enhanced, 10 attributes need to be maintained, 2 attributes do not effect consumer satisfaction less, and 1 attribute has to be reduced in intensity.